A preliminary investigation into the evaluation of possession-based small-sided games and the influence of decision-making ability in identifying talented pre-pubertal soccer players - Fenner, J.; Doncaster, G.; McRobert, A.; Ford, P.; Iga, J.; Unnithan, V. (Apunts Sports Medicine, 2022)
Introduction The aims of this study were 1) to assess if talented players can be identified within possession-based small-sided games (SSG), and 2) to determine if, decision making, physical, and time-motion characteristics correlated to success in a possession-based SSG.